Optimization and modeling of arsenic removal from groundwater by recirculated batch electrodialysis - Mendoza, Rose Marie O. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Arsenic-related health conditions in several countries including the Philippines and Taiwan have been earning global interest for decades. Arsenic in its aqueous form is odorless and tasteless which makes its presence in drinking water undetected. In this study, inorganic arsenic in groundwater was removed using a novel electrodialysis (ED) stack. The limiting current density for the stack was found to be 0.0899 mA/cm2. The effects of experiment parameters such as applied potential, initial feed concentration and feed flow velocity on arsenic removal were also investigated. Arsenic removal efficiency directly varies with applied potential, initial feed concentration and separation time but slightly varies with feed flow velocity, while current utilization have an inverse linear relationship with arsenic removal. The removal of arsenic from As-spiked water and actual ground water follows Yu and Admassu's second order homogenous ordinary differential equation (ODE) model for the removal of metal ion from pulp and paper mill process. The optimization of the experimental parameters was performed using the Taguchi L9 Orthogonal Array followed by ANOVA. Optimum conditions showed that the process can perform at as high as 99.2% +- 0.36% arsenic removal efficiency at an applied potential of 17V, feed flow velocity of 0.033 l/s (2.0 l/min), initial feed concentration of up to 70 µg/l and separation time of 92 min. The average total inorganic arsenic in the product water is 3.08 µg/l which is lower than the maximum contaminant level (MCL - 10 µg/l set by WHO and US EPA for Arsenic in drinking water.
Dissertation (Ph. D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Groundwater -- Purification -- Arsenic removal; Sewage -- Purification -- Electrodialysis process